The Effect of using the 5E Instructional Strategy in developing critical thinking skills for third-grade intermediate students in the jurisprudence course - Al- Muhammadi, Ahlam Merji (Journal of Educational and Psychological Sciences, 2021)
This study investigates the effect of the 5E Instructional strategy on the development of critical thinking skills of intermediate third graders through Jurisprudence course compared to the normal way of teaching. In order to achieve this goal the researcher adopted a pre- post two- group (experimental and control) quasi- experimental research methodology. The tool of the study was a critical thinking skills test based on Mary McFarland's strategy. After the validation and calculation of the tool's reliability, the researcher piloted the tool at a random sample consisting of (63) female intermediate third graders in thirtieth Medina School. The study used a number of appropriate statistical analyses which included: means of scores, standard deviation, alpha Cronbach coefficient reliability test of critical thinking skills, and T- test for independent samples to ensure group homogeneity of study groups, and to see the effect of using the 5E Instructional strategy on developing the critical thinking skills of the students. The obtained results indicated that there are statistically significant differences at the level of significance (a = 0.05) between the mean scores of experimental group and control group students in the critical thinking skills test in favor of the experimental group. In the light of these results, a number of recommendations have been made, namely: religious science teachers should be supervised towards more attention to the development of critical thinking skills; paying attention to the involvement of the student in the learning process; encouraging students to express their opinions and being able to defend their point of view in order to increase the level of critical thinking skills and finally to employ the 5E Instructional strategy in teaching jurisprudence course. Based on the findings of the study, a group of suggestions for future studies have been made that can be considered as extension to the current study.
Keywords: Five- E's Learning Cycle Strategy; critical thinking skills; third intermediate grade; jurisprudence course